Increasing the loyalty of cooperative members : The influence of sharia compliance, employee responsibility, and trust - Alfiana, Alfiana; Hanifah, Luluk (LPMP Imperium, 2025)
This study examines the determinants of cooperative member loyalty through the lens of Sharia compliance, employee accountability, and trust. The research methodology used quantitative analysis. Data collection methods included questionnaires and structured interviews with 80 research participants. The population consisted of all Ikhlas Beramal Bangkalan Islamic marketing cooperative members. In addition, the data from these respondents were analyzed using SPSS software. Analysis of the research data shows that Sharia compliance shows a negative correlation and does not significantly affect member loyalty. In contrast, employee responsibilities positively correlate with and significantly affect member loyalty. In addition, trust shows a negative correlation and significantly impacts member loyalty. The three elements collectively influence the loyalty of the Ikhlas Beramal Bangkalan Sharia marketing cooperative members. Public interest statement Since employee accountability positively impacts loyalty, cooperatives should prioritize staff training to improve professionalism and service quality. The negative effect of Sharia compliance and trust suggests a need to reassess its implementation, ensuring alignment with member expectations through more transparent communication and better integration.